2009
DOI: 10.1097/mpg.0b013e318183138a
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the IBD5 Locus Are Associated With Crohn Disease in Pediatric Ashkenazi Jewish Patients

Abstract: Objectives: To analyze the IBD5 locus in a homogenous cohort of Ashkenazi Jewish (AJ) children with Crohn disease (CD). Patients and Methods: A total of 83 AJ children with CD and 73 AJ healthy controls were studied. Genotyping for single nucleotide polymorphisms (SNPs) including OCTN1 (SLC22A4; 1672C!T), OCTN2 (SLC22A5; 207G!C), IGR2096, IGR2198, and IGR2230 genes was performed using the TaqMan system. NOD2/CARD15 variants also were typed using established methods. Results: All IBD5 SNPs tested were in linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…In the case of OCTN, Peltekova et al [4] reported an association between the TC haplotype of OCTNs consisting of two genetic variants, OCTN1, L503F and OCTN2, g.-207G>C and susceptibility to CD. This finding was validated by several other association studies [14][15][16][17][18][19][20][21][22]. However, previous studies reported that these two variants are not found in Asian populations [17][18][19].…”
Section: Original Articlesupporting
confidence: 72%
“…In the case of OCTN, Peltekova et al [4] reported an association between the TC haplotype of OCTNs consisting of two genetic variants, OCTN1, L503F and OCTN2, g.-207G>C and susceptibility to CD. This finding was validated by several other association studies [14][15][16][17][18][19][20][21][22]. However, previous studies reported that these two variants are not found in Asian populations [17][18][19].…”
Section: Original Articlesupporting
confidence: 72%
“…Peltekova et al 20 had shown that haplotypes consisting of at least one of the p.503Phe or c.-207C alleles on the nonrisk-associated IBD5 background (defined by IGR2078a_1) were more frequent in patients compared to controls, and based on this finding and functional studies, these variants in SLC22A4 and SLC22A5 genes were proposed to be causal. Similar to several previous studies, 21,22,29,[39][40][41] we did not confirm this finding; the power to detect the associations was, however, borderline. In our dataset, neither variants in SLC22A4 and SLC22A5 were associated with CD independently of IGR2063b_1 as the strongest associated SNP within IBD5.…”
Section: Discussioncontrasting
confidence: 61%
“…Indeed, genetic polymorphisms of polyspecific organic cation transporters OCTN1/2, translocating cytoplasmic serotonin through the cytoplasmic membrane, are among the CD predisposition factors [ 85 , 86 ]. Moreover, the CD-associated OCTN1 and NOD2 gene polymorphisms are additive for CD development [ 87 ].…”
Section: Introductionmentioning
confidence: 99%